2013
DOI: 10.1242/jcs.140723
|View full text |Cite
|
Sign up to set email alerts
|

The conserved ciliary protein Bug22 controls planar beating ofChlamydomonasflagella

Abstract: Eukaryotic flagella and cilia can exhibit planar and non-planar beating, and the mechanism controlling these beating patterns is not well understood. Chlamydomonas reinhardtii flagella beat in approximately the same plane with either an asymmetric ciliary-type or symmetric flagellar-type waveform. Each B-tubule of the number 1, 5 and 6 doublets of the flagellar axoneme possesses a beak-like structure. The number 5 and 6 beak structures are implicated in conversion of ciliary motion into flagellar motion. Here,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
47
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 33 publications
(47 citation statements)
references
References 35 publications
0
47
0
Order By: Relevance
“…Such observations may reflect the polarized nature of the flagellar axoneme. For example, the beak-like structures within doublet microtubules are found only in the proximal part of flagella (Hoops and Witman, 1983), as are the polyglutamylated tubulins (Kann et al, 2003) and the axonemal protein Bug22 (Meng et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Such observations may reflect the polarized nature of the flagellar axoneme. For example, the beak-like structures within doublet microtubules are found only in the proximal part of flagella (Hoops and Witman, 1983), as are the polyglutamylated tubulins (Kann et al, 2003) and the axonemal protein Bug22 (Meng et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…The disrupted genes were identified by cloning the flanking genomic sequences using RESDA PCR followed by sequencing [54, 55]. The DNA fragment with about 250 nt being deleted from 5’ end has replaced the nucleotides 215–221 of the IFT43 gene.…”
Section: Methodsmentioning
confidence: 99%
“…For palmelloid cells, the cells were treated with gametic autolysin to release the daughter cells followed by DIC microscopy. A previous procedure was used to examine the ultrastructure of the flagella by thin section EM [55, 59]. …”
Section: Methodsmentioning
confidence: 99%
“…The flanking sequence of the DNA insert was identified by RESDA PCR and sequencing (González-Ballester et al, 2005;Meng et al, 2014). To make a construct for rescuing kcn11, the KCN11 gene with an ∼2 kb fragment upstream of the start codon was cloned by PCR using Phanta Max Super-Fidelity DNA Polymerase (Vazyme Biotech Co. Ltd, Nanjing, China) from a bac clone BAC31O7 (Clemson University, USA) and a 3×HA tag sequence followed by a LC8 terminator was cloned from plasmid pKL-3xHA (kindly provided by Karl F. Lechtreck, University of Georgia, Athens, GA) (Lechtreck et al, 2009).…”
Section: Insertional Mutagenesis Gene Cloning and Other Molecular Tmentioning
confidence: 99%
“…To analyze the function of the new proteins, C. reinhardtii insertional mutants were generated by transforming with a DNA fragment harboring the paromomycin-resistance gene AphVIII (Meng et al, 2014;Sizova et al, 2001). We found that KCN11 was disrupted in one of the mutants by the insertion of this DNA fragment in the sixth exon of the gene (Fig.…”
mentioning
confidence: 99%